2021
DOI: 10.1016/j.jcot.2021.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Elbow arthroscopy - Indications and technique

Abstract: Throughout the years, elbow arthroscopy has advanced tremendously due to improvements in technology and surgical techniques. It is now considered a safe and effective treatment for a variety of elbow disorders. Due to the small working space and nearby neurovascular structures, it is a technically challenging procedure. It can be used to successfully treat complaints caused by loose bodies, osteoarthritis, arthrofibrosis, OCD, lateral epicondylitis, VEOS and fractures. The most devastating complication of elbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Radicular symptoms originating from the elbow may suggest nerve compression (cubital tunnel syndrome, radial tunnel syndrome, or flexor pronator syndrome). Specific history questions should also inquire about patient occupation (e.g., manual laborer) and sports activities (e.g., weight lifter, thrower, gymnast) [1][2][3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Radicular symptoms originating from the elbow may suggest nerve compression (cubital tunnel syndrome, radial tunnel syndrome, or flexor pronator syndrome). Specific history questions should also inquire about patient occupation (e.g., manual laborer) and sports activities (e.g., weight lifter, thrower, gymnast) [1][2][3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
“…An incompetent lateral UCL may be assessed with a pivot shift maneuver of the elbow or a push-up from a seated position in an armed chair. These tests may reproduce subluxation of the radial head that is both visible and palpable [1][2][3][4][5] .…”
Section: Physical Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Pu et al concluded that a combination of radiography, computed tomography (CT), and magnetic resonance imaging (MRI) can most accurately determine OCD lesion stability by compensating for the respective flaws of the individual modalities [ 18 ]. However, at present, surgery is the only means of conclusively confirming the severity of OCD lesions using the classification proposed by the International Cartilage Repair Society (ICRS) [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%